Effects of acute sodium bicarbonate supplementation on anaerobic performance in elite and non-elite male cyclists - Armin Mohammadi Gajvati; Saeed Nikokheslat; Javad Vakili; Ramin Amirsasan; میرمعصوم سهرابی (Journal of Sport & Exercise Physiology (JSEP) / Fīziyuluzhī-i Varzish va Fa̒āliyyat-i Badanī, 2020)
Purpose: Sodium bicarbonate with buffering effect is one of the additives and effective supplement to reduce fatigue. Therefore, the main objective of the present study is to investigate the acute effect of sodium bicarbonate supplementation on anaerobic performance in elite and non-elite male cyclists. Methods: In a single-blind crossover study 12 semi endurance elite cyclist (with 3 year national and international competitions experience) and 16 non-elite cyclists (no history of official competition) in the range of 17 – 29 years old selected purposefully and were placed in two group. Both group within one week, 60 minutes before the test, consumed 100 mg placebo (NaCl) or 300 mg sodium bicarbonate per kg of body weight of dissolved in 200 ml of water. The Wingate anaerobic test, measure participants peak power, average power, power drop and recovery heart rate indexes and the results were analyzed by using analysis variance (2 × 2) (p <0.05). Results: dependent variables response to sodium bicarbonate supplementation had no significant difference between two groups (p >0.05), However, in both group the acute supplementation of sodium bicarbonate result in a significant increase in peak power (P<0.001) and average power (P=0.001) and result in a significant decrease in power drop (P<0.001) and fifth minute recovery heart rate (P<0.001). Conclusion: According to improvement of anaerobic capacity of elite and non-elite male cyclists following acute supplementation of sodium bicarbonate, its effectiveness is possible regardless fitness level or muscle buffering capacity.